Motivations for methamphetamine cessation among young people in northern Thailand - Danielle German (2018)
Aim: To understand factors influencing cessation intentions among young Thai methamphetamine (MA) users, a population with dramatically increasing rates of MA use. Design and participants: A total of 48 in-depth interviews conducted between March 2002 and January 2003 with current and recent MA users aged 15-29 years. Setting: Chiang Mai city and surrounding district, Thailand. Measurement: Interviews addressed family history, drug use patterns and influences, cessation history, drug treatment experiences and sexual behavior. Data were analyzed inductively using the constant comparative method common to grounded theory methods. Atlas-ti was used for data management. Findings: Cessation intentions were motivated by a range of internal and external influences, including attitudes towards continued MA use shaped by recognition of negative impact on self and others; influence of family, peers, partners and community stigma; perceptions on cessation and drug treatment; and external facilitators and situational barriers, such as extensive peer pressure and drug availability. In most cases, multiple factors operated simultaneously. Some variation according to duration of use and treatment status was observed. Conclusions: Evidence-based interventions addressing MA use among Thai young people are urgently needed. These data support the continuation of evidence-based drug treatment at levels adequate to address the population need and implementation a multi-faceted approach that aims to enhance identified cessation influences in this population and minimize contextual barriers to cessation. © 2006 The Authors.